2021
DOI: 10.1155/2021/6642983
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 Promotes Pancreatic Differentiation In Vitro by Affecting Different Target Genes at Different Stages

Abstract: Human embryonic stem cells (hESCs) possess the ability to differentiate into insulin-producing cells (IPCs), which can be used to treat type I diabetes. miR-375 is an essential transcriptional regulator in the development and maturation of the pancreas. In this study, we optimized a protocol to differentiate hESCs into IPCs and successfully obtained IPCs. Then, we performed overexpression and inhibition experiments of miR-375 on cells at different stages of differentiation and performed RNA-seq. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…24 In consistent, the recent study indicated that miR-375 promotes pancreatic differentiation in vitro by affecting different target genes at different stages. 25 Since CSCs always share the same survival mechanisms with normal stem cells, miR-375 was regarded to be involved in CSC progression, which was further confirmed by several studies. 5,6,26 Besides, miR-375 was indicated to exert anti-tumorigenic effects via regulating tumor microenvironment (TME).…”
Section: Circrpph1 Acts As An Mir-375 Sponge In Gc Cellsmentioning
confidence: 80%
See 1 more Smart Citation
“…24 In consistent, the recent study indicated that miR-375 promotes pancreatic differentiation in vitro by affecting different target genes at different stages. 25 Since CSCs always share the same survival mechanisms with normal stem cells, miR-375 was regarded to be involved in CSC progression, which was further confirmed by several studies. 5,6,26 Besides, miR-375 was indicated to exert anti-tumorigenic effects via regulating tumor microenvironment (TME).…”
Section: Circrpph1 Acts As An Mir-375 Sponge In Gc Cellsmentioning
confidence: 80%
“…MiR‐375 has been shown to control normal stem cell differentiation, such as miR‐375 controls porcine pancreatic stem cell fate by targeting 3‐phosphoinositide‐dependent protein kinase‐1 (Pdk1) 23 ; Overexpression of miR‐375 promotes the differentiation of human‐induced pluripotent stem cells into hepatocyte‐like cells 24 . In consistent, the recent study indicated that miR‐375 promotes pancreatic differentiation in vitro by affecting different target genes at different stages 25 . Since CSCs always share the same survival mechanisms with normal stem cells, miR‐375 was regarded to be involved in CSC progression, which was further confirmed by several studies 5,6,26 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the overexpression of miR-375 in MIN6 cells could inhibit glucose-induced insulin secretion. Thus, miR-375 could be a potential biomarker for the treatment of diabetes [ 100 ]. In cancer cells, glucose is preferentially metabolized through aerobic glycolysis, increasing the production of glycolysis and lactic acid.…”
Section: Mir-375 As a Potential Diagnostic Or Prognostic Biomarkermentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous small-non-coding RNAs, which act as crucial regulatory roles in gene expression by complementary binding to the 3'-untranslated regions (3'-UTR) of target mRNAs [8]. Numerous evidences have supported that miRNAs are involved in the differentiation of various stem cells into IPCs by regulating target genes [9][10][11]. For instance, miRNA-375 promoted the differentiation of human embryonic stem cells into IPCs by affecting its target genes and pancreatic development-related genes, including PDPK1, INSM1, HNF1B, GATA6, NOTCH2, PAX6, and CADM1 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidences have supported that miRNAs are involved in the differentiation of various stem cells into IPCs by regulating target genes [9][10][11]. For instance, miRNA-375 promoted the differentiation of human embryonic stem cells into IPCs by affecting its target genes and pancreatic development-related genes, including PDPK1, INSM1, HNF1B, GATA6, NOTCH2, PAX6, and CADM1 [9]. miRNA-690 facilitated the differentiation of induced pluripotent stem cells into IPCs by targeting Sox9 [11].…”
Section: Introductionmentioning
confidence: 99%